2014
DOI: 10.1371/journal.pone.0098133
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Tribe Theeae (Theaceae s.s.) and Its Implications for Generic Delimitation

Abstract: Tribe Theeae, which includes some economically important and widely grown plants, such as beverage tea and a number of woody ornamentals, is the largest member of the Theaceae family. Using five genomic regions (chloroplast: atpI-H, matK, psbA5'R-ALS-11F, rbcL; nuclear: LEAFY) and 30 species representing four of the five genera in this tribe (Apterosperma, Camellia, Polyspora, and Pyrenaria s.l.), we investigated the phylogeny of Theeae and assessed the delimitation of genera in the tribe. Our results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
0
25
2
1
Order By: Relevance
“…The nrDNA internal transcribed spacer (ITS) region and chloroplast DNA have higher variability and are thus suitable for classifying lower taxonomic levels [ 24 , 25 , 26 ]. Accordingly, these regions are useful for inferring phylogenetic relationships at lower taxonomic levels and have been successfully used to analyze plant systematics [ 27 , 28 ]. Here we selected three cpDNA termed the rbc L gene, mat K gene and trn L-F gene and one nrDNA ITS to study the interspecific relationships [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nrDNA internal transcribed spacer (ITS) region and chloroplast DNA have higher variability and are thus suitable for classifying lower taxonomic levels [ 24 , 25 , 26 ]. Accordingly, these regions are useful for inferring phylogenetic relationships at lower taxonomic levels and have been successfully used to analyze plant systematics [ 27 , 28 ]. Here we selected three cpDNA termed the rbc L gene, mat K gene and trn L-F gene and one nrDNA ITS to study the interspecific relationships [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Theeae is the most diverse of these tribes and contains Camellia, Polyspora, Pyrenaria, Apterosperma, and Laplacea. A recent molecular phylogenetic analysis of Theeae indicated that Camellia and Pyrenaria form a paraphyletic group; these two occur and hybridize naturally with each other (Zhang et al, 2014). Gordoniae and Stewartiae belong to the sister clade of Theeae.…”
Section: Taxonomy/systematicsmentioning
confidence: 99%
“…Additional fossil evidence, however, is required to show the validity of this suggestion. The molecular dating of diversification events within the tribe Theeae (Zhang et al 2014) used the fruits and seeds of Andrewsiocarpon henryense Grote et Dilcher from the middle Eocene Claiborne Formation of western Kentucky and Tennessee, USA (Grote and Dilcher 1989) and wood of Camellia japonoxyla from the lower Miocene Yanagida Formation of Japan (Suzuki and Terada 1996) for calibration and estimated the time of Camellia radiation as ca. 22 Ma, i.e.…”
Section: Phytogeographical Implicationsmentioning
confidence: 99%